Analisis Literatur Jurnal Pada Variasi Pengendalian Mikroorganisme - Khairani, Miftahul; Damanik, Alfina Sukma Hayati; Lubis, Isnaini Rahmah; Nabilla, Mutiara; Nahombang, Syntia Zeyrani (Philosophiamundi, 2025)
This research discusses various methods of controlling microorganisms through literature analysis from various scientific journals. Microorganisms including bacteria, viruses, fungi, algae and protozoa can have positive or negative impacts. For this reason, controlling microorganisms is important in order to maximize their benefits and minimize their negative impacts. This study describes the effectiveness of various control techniques, including biological, chemical, and physical approaches. This analysis is expected to provide new insights regarding innovative and environmentally friendly methods of controlling microorganisms, relevant for various fields such as health, industry and agriculture, while maintaining the balance of the microbial ecosystem